Impact of hepatitis C virus infection on long-term mortality after acute myocardial infarction: a nationwide population-based, propensity-matched cohort study in Taiwan. Issue 1 (26th January 2018) - Kuo, Shu-Hung; Hung, Wang-Ting; Tang, Pei-Ling; Huang, Wei-Chun; Yang, Jin-Shiou; Lin, Hsiao-Chin; Mar, Guang-Yuan; Chang, Hong-Tai; Liu, Chun-Peng
Abstract : Introduction: The influence of hepatitis C virus (HCV) infection on long-term outcomes of patients with acute myocardial infarction (AMI) is unclear. Therefore, this study aimed to analyse the impact of HCV infection on 12-year mortality rates after AMI using data from the Taiwan National Health Insurance Research Database (NHIRD). Methods: NHIRD data for approximately 23 000 000 patients between January 2000 and December 2012 were analysed. A total of 186 112 cases of first AMI admission were identified. A total of 4659 patients with HCV infection not receiving interferon therapy were enrolled and divided into those with (n=107) or without (n=4552) cirrhosis. Using one-to-one matching, 4552 matched controls were included in the final analysis. Results: The 12-year mortality rate was significantly higher in patients with AMI with HCV infection and cirrhosis than in those with HCV infection but without cirrhosis (P<0.0001) or controls (P<0.0001). Patients with HCV infection but without cirrhosis had significantly higher long-term mortality rates than the matched controls (P<0.0001). The HR for mortality was higher in patients with HCV infection (HR 1.12; 95% CI 1.06 to 1.18). HCV influenced outcomes among the subgroups of patients who were male (HR 1.15) and those who had hypertension (HR 1.14). Conclusions: HCV infection influenced the 12-year mortality rates of patients with AMI, especially those who were male and those who had hypertension. Cirrhosis further increased the long-term mortality rates of patients with AMI with HCV infection.